THE USE OF PRINTED AND DIGITAL READING MATERIALS IN ENGLISH LANGUAGE LEARNING AT MTS NURUL HARAMAIN: A COMPARATIVE ANALYSIS - SAFNA, RIA; THOHIR, LALU; AMIN, MUHAMMAD; ELMIANA, DEWI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
The purpose of the study is to find out the students’ perceptions on Printed and Digital reading materials at MTs Nurul Haramain and to know which type of reading materials is more preferred by those students. This research applied mixed method with sequential explanatory design. Out of 5 classes at MTs Nurul Haramain, 1 class (class A which consist of 30 students) was chosen purposively because of the students in this class used both printed and digital reading material more frequently than other classes. To collect the data needed, questionnaire and interview were used. The data obtained from questionnaire were analyzed quantitatively in the form of percentages and those data obtained from observation and interviews were analyzed qualitatively through data condensation, data display and conclusion drawing/verification. The result of this research showed that the students were in neutral stance toward printed reading materials. There was some recognition of their advantages, such as ease of reading and focus, there was no overwhelming preference. About half of the students were in neutral stance regarding the use of printed materials for various activities, with a slight inclination towards agreement on their benefits for assignments. Further, the students hold a neutral view toward digital reading materials. Some of them appreciated their practicality, most of them remain indifferent or hesitant, particularly when they used it for assignments and exam preparation. Despite recognizing certain benefits, many students still preferred or leaned toward traditional printed materials because they recognized certain benefits of this type of learning materials and they were more uncertain or had mixed feelings about the advantages of digital formats. ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui persepsi siswa terhadap bahan bacaan Cetak dan Digital di MTs Nurul Haramain dan mengetahui jenis bahan bacaan mana yang lebih disukai oleh siswa tersebut. Penelitian ini menggunakan metode campuran dengan desain eksplanatif sekuensial. Dari 5 kelas di MTs Nurul Haramain, 1 kelas (kelas A yang terdiri dari 30 siswa) dipilih secara purposif karena siswa di kelas ini lebih sering menggunakan bahan bacaan cetak dan digital dibandingkan kelas lainnya. Untuk mengumpulkan data yang diperlukan digunakan kuesioner dan wawancara. Data yang diperoleh dari kuesioner dianalisis secara kuantitatif dalam bentuk persentase dan data yang diperoleh dari observasi dan wawancara dianalisis secara kualitatif melalui kondensasi data, display data, dan penarikan kesimpulan/verifikasi. Hasil penelitian ini menunjukkan bahwa siswa bersikap netral terhadap bahan bacaan cetak. Ada beberapa pengakuan atas kelebihannya, seperti kemudahan membaca dan fokus, tidak ada preferensi yang berlebihan. Sekitar setengah dari siswa bersikap netral mengenai penggunaan bahan cetak untuk berbagai kegiatan, dengan sedikit kecenderungan menyetujui manfaatnya untuk tugas. Selain itu, siswa mempunyai pandangan netral terhadap bahan bacaan digital. Sebagian dari mereka mengapresiasi kepraktisannya, sebagian besar masih acuh tak acuh atau ragu-ragu, terutama ketika digunakan untuk tugas dan persiapan ujian. Meskipun menyadari adanya manfaat tertentu, banyak siswa masih lebih memilih atau condong ke bahan cetak tradisional karena mereka menyadari manfaat tertentu dari bahan pembelajaran jenis ini dan mereka lebih ragu atau memiliki perasaan campur aduk mengenai manfaat format digital.